Application of Chemometrics-assisted HPLC-DAD Strategies for Simulta-neous Determination of Paracetamol, Pseudoephedrine HCl, Dextrome-thorphan HBr, Doxylamine Succinate and Saccharin in Syrup Formulation - Dinc-Zor, Sule; Donmez, Ozlem Aksu; Bozdogan, Abdurrezzak E. (BENTHAM SCIENCE PUBL LTD, 2021)
Introduction: This study introduces an effective strategy, which combines high performance liquid chromatography coupled with diode array detection (HPLC-DAD) with multivariate calibration methods for the simultaneous determination of paracetamol (PAR), pseudoephedrine HCl (PSE), dextromethorphan HBr (DEX) and doxylamine succinate (DOX) along with sweetener saccharin (SAC) in syrup formulation. Methods: PLS-2 and PCR calibration algorithms were selected for data processing. Based on the strategy, all target analytes were rapidly quantified within 5.3 min under the simple isocratic elution (water: methanol, 20/80, v/v) without a complete separation. The performances of the proposed methods were confirmed by analyzing a series of synthetic solutions including different concentrations of analytes. Results: The average recovery values were in the range of 100.33 to 103.70%, and the REP (relative error of prediction) values ranged from 1.96 to 4.36% showed that these methods could provide satisfactory predictions. Conclusion: Novel HPLC methods coupled with PLS and PCR algorithm enable a simple, fast and low-cost analysis of similar pharmaceutical products for simultaneous determination of the target compounds.
Keywords: Multivariate calibration; HPLC-DAD; multicomponent analysis; saccharin; syrup; paracetamol; PERFORMANCE LIQUID-CHROMATOGRAPHY; INTERFERENCE-FREE DETERMINATION; CALIBRATION; INGREDIENTS; MIXTURE; 3-WAY; FOOD; Pharmacology & Pharmacy